PENDUGAAN KANDUNGAN KARBON LIMBAH BATANG POHON KELAPA SAWIT PEREMAJAAN KEBUN DI PROVINSI RIAU - Endro Siswoko; Aras Mulyadi; Thamrin Thamrin; Bahruddin Bahruddin (Program Pascasarjana Universitas Riau, 2017)
Until 2009, Riau Province had lost more than four million hectares of forest. The loss of forest coverage was caused by several reasons, such as forest area converted into oil palm plantation (29%), converted into industrial forest (24%) and abandoned deforested land (17%) which was not replaced by any other plants. Up until 2016, Riau Province ranked first in oil palm plantation development with area of 2,430,508 hectares and total of 534,827 workers. The largest amount of replanting activity waste came from oil palm trunks. The treatments of oil palm trunks waste by burning as well as decomposing were considered wasteful and costly. This also leads to a massive carbon emission in the atmosphere, which would cause global warming. Currently, CO2 gas concentration is 40% higher compared to pre-industrial era mainly due to fossil fuel incineration and deforestation. This research aims to measure the dry weight and the amount of carbon and carbon dioxide stock within oil palm trunks waste, as a consideration in taking a policy on preventing and or reducing carbon released to the atmosphere. Oil palm trunks waste came from PT. Perkebunan Nusantara V Persero (state-owned) plantation in Tandum, Riau Province. Data for measuring dry weight and the amount of carbon and carbon dioxide stock was taken randomly from three oil palm trunks. Every trunk was divided into three part (lumbers) which represent the base, middle, and top part of the trunk. Based on the research result, the weight of dry oil palm trunks averages 394.11 kg/tree or 50.45 ton/ha. Carbon stock on oil palm’s biomass averaging at 223.68 kg C/tree or 28.63 ton C/ha, equivalent to 104.97 ton CO2/ha of carbon dioxide stock. The dry weight and the amount of carbon and carbon dioxide in base trunk part are higher than the middle, and the middle part was higher than the top. This data indicates that the base part of the trunk contain the highest amount of biomass and carbon and carbon dioxide stock.